Pre-hospital determinants of outcome in traumatic brain injury: Experiences from first comprehensive integrated pre-hospital care providers in India: GVK — EMRI Experience - Saxena, Mukul Kumar; Saddichha, Sahoo; Pandey, Vibha; Rahman, Abdur (Indian Journal of Neurotrauma, 2010)
Indian studies have reported that nearly 1.5 to 2 million persons are injured and 1 million succumb to death every year in India due to traumatic brain injury. Road traffic injuries are the leading cause (60%) of TBIs followed by falls (20%-25%) and violence (10%).It is also a known fact that the best facilities, equipment and skill sets in terms of emergency room, ICU facilities, neurosurgical skills and equipment cannot reverse damage sustained at scene of injury or enroute to hospital. Airway obstruction and aspiration are major cause of death in treatable head injuries. The aims of prevention of secondary brain injury can be met with only in pre-hospital settings. All these facts underscore the need for an efficient pre-hospital care management of head injuries. However, in India, till 2005, no comprehensive data has been available on this aspect of management, because there was no integrated comprehensive pre-hospital care providing service available. In 2005, Emergency Management and Research Institute (EMRI) was established, to take a lead role in providing pre-hospital care. We wish to share our experience and the findings in pre hospital management of Traumatic Brain Injuries(TBI).This is retrospective study of 1607 cases of traumatic brain injury handled by EMRI, in the state of Andhra Pradesh, from 01 Jan 08 to 31 Dec 08. Data captured on patient case report forms (PCR) for this segment of emergencies was reviewed. We studied various components of the data having a bearing on outcome, namely the social, demographic, clinical determinants, response times and outcome.The demographic determinants reveal that incidence of head injury in men is more than twice that in women. It is the people in prime of their age (21–45) who are affected most. The share of victims handled by EMRI shows a preponderance of economically deprived population amongst victims. Analysis of different risk factors revealed that systolic BP at scene and at hospital is significantly correlated with outcome. Paired sample T-test showing a 2-tailed significance of P<0.01at 95 % CI: 3.717–8.777, with T value of 4.843. GCS analysis revealed significant correlation with outcome at level of p<0.01, with Pearson's ‘R’ value of. 071. Age of victim showed significant correlation at p<0.05 level with Pearson's R value of.087. SPO2 showed significant correlation with outcome with a significance at level of p < 0.01, and Pearson's ‘R’ value of 0.217. The mean response time was found to be statistically significant at p<0.05 level and a ‘Pearson's R’ value of .094. One way Anova studies showed distance to be significant at P< 0.05 level at 95 % CI: 16.56–43.35, with a f value of 4.376.It is evident from the study that the analysis of risk factors leading to establishing guidelines and protocols for pre hospital management of head injuries can definitely contribute to improving outcomes in TBI.
Keywords: EMRI; Pre-hospital management; traumatic brain injury; vehicular accidents